Transcriptional factor 3 binds to sirtuin 1 to activate the Wnt/β-catenin signaling in cervical cancer. Issue 5 (2nd May 2022) - Yu, Xiao; Li, Zhaoshuo; Bai, Ruihua; Tang, Fuxiang
ABSTRACT: Transcriptional factor 3 (TCF3, also termed E2A), first reported to exert crucial functions during lymphocyte development, has been revealed to participate in the pathogenesis of human cancers. The aim of this work was to investigate the function of TCF3 in cervical cancer (CC) and the molecular interactions. The bioinformatics prediction suggested that TCF3 was highly expressed in CC and linked to poor prognosis. Increased TCF3 expression was identified in CC cell lines, and its downregulation reduced proliferation and migration of CC cells in vitro as well as growth of xenograft tumors in vivo . Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses showed that the TCF-3-related genes and genes showed differential expression between CC and normal tissues were mainly enriched in the Wnt/β-catenin pathway. TCF3 bound to sirtuin 1 (SIRT1) promoter for transcriptional activation, and SIRT1 promoted deacetylation and nuclear translocation of β-catenin in CC. SIRT1 overexpression blocked the role of TCF3 silencing and restored cell proliferation in vitro and tumor growth in vivo . Treatment with XAV-939, a β-catenin inhibitor, significantly suppressed the cell proliferation and tumor growth induced by SIRT1 overexpression. In conclusion, this study demonstrates that TCF3 augments progression of CC by activating SIRT1-mediated β-catenin signaling. GRAPHICAL ABSTRACT: uf0001